Perancangan Dan Impelementasi Sistem Penjualan Berbasis Web Menggunakan Metode Prototype (Studi Kasus : Allawn Archery) - Muhammad Fazil Abdillah Fazil; Pari Purnaningsih (CV. Multi Kreasi Media, 2022)
Allawn Archery is a traditional archery shop. On the other hand, Allawn archery wants to make the store wider in its scope of business. Currently, Allawn archery does not have a special website for selling their products. Product orders are made by sending a message via Whatsapp (WA) and the order data collection is recorded in hard copy format and then inputted into application spreadsheet. This is certainly less effective in terms of time because the sales department of Allawn archery is currently only managed by one (1) person. The method used to design this web-based online store information system is Prototype. The first stage is to analyze the system requirements and then the design stage using UML diagrams. This web-based online store information system is designed and built using the CodeIgniter v.4 framework and MySQL database as data storage. The result of this research is an information system designed to be able to process information related to the sale of Allawn archery products and to process all purchase transaction data for Allawn archery products